Integral Transforms of Pragathi-Satyanarayana’s I - function - duvvuri, krishna pavan kumar (Communications in Mathematics and Applications, 2025)
Many of the transformations like Euler, Hankel, Sumudu and K-transforms plays a vital role in the field of engineering mathematics and has many applications. This paper refers to the study of Pragathi-Satyanarayana I-function of one variable. As a part of this study, we obtain different integral transforms of Pragathi-Satyanarayana I-function of one variable. Also some of the generalized transforms has been obtained as special cases. The integral transformations developed here are useful in real-world applications of mathematical science.